2017
DOI: 10.1038/s41598-017-16780-w
|View full text |Cite
|
Sign up to set email alerts
|

Preferential selection of Arginine at the lipid-water-interface of TRPV1 during vertebrate evolution correlates with its snorkeling behaviour and cholesterol interaction

Abstract: TRPV1 is a thermo-sensitive ion channel involved in neurosensory and other physiological functions. The trans-membrane helices of TRPV1 undergo quick and complex conformational changes governed by thermodynamic parameters and membrane components leading to channel opening. However, the molecular mechanisms underlying such events are poorly understood. Here we analysed the molecular evolution of TRPV1 at the lipid-water-interface region (LWI), typically defined as a layer of 6 Å thickness on each side of the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 99 publications
(105 reference statements)
3
28
0
4
Order By: Relevance
“…We found that the treatment with extracellular MCD decreased the maximal response of mTRPA1 channels to AITC, which can be readily explained by the reduced channel expression at the plasma membrane (Figure 7), as has been reported for TRPV1 (Liu et al, 2006; Saha et al, 2017) and TRPV4 (Lakk et al, 2017). We also found that, surprisingly, the extracellular MCD treatment strongly reduced the sensitivity of TRPA1 to chemical stimulation with AITC (a 5-fold increased EC 50 ).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…We found that the treatment with extracellular MCD decreased the maximal response of mTRPA1 channels to AITC, which can be readily explained by the reduced channel expression at the plasma membrane (Figure 7), as has been reported for TRPV1 (Liu et al, 2006; Saha et al, 2017) and TRPV4 (Lakk et al, 2017). We also found that, surprisingly, the extracellular MCD treatment strongly reduced the sensitivity of TRPA1 to chemical stimulation with AITC (a 5-fold increased EC 50 ).…”
Section: Discussionsupporting
confidence: 79%
“…Regarding the role of cholesterol-channel interactions in membrane localization, it was previously observed that mutations in putative cholesterol binding sites in TRPV1 produced proteins that were largely retained intracellularly (Saha et al, 2017). However, it was not reported whether those mutations actually resulted in functional channels, nor whether there was a disturbed pattern of expression at the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Protein molecules, including TRPV1, are expected to gain complexity in their functions during evolution 14,15 . To discover TRPV1 channels with a simpler heat response, we focused on primitive mammals by carrying out evolutionary analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Increased membrane cholesterol, but not its diastereoisomer epicholesterol addition, inhibited CAPS-, heat-and voltage-induced TRPV1 currents (Picazo-Juárez et al, 2011). These results were also supported by structural studies of CRACs (Levitan et al, 2014;Saha et al, 2017).…”
Section: Discussionmentioning
confidence: 53%